A zsarnokölésről, avagy jogszerű-e a zsarnok elpusztítása? - Dobozi, Gergely Ferenc (Debreceni Jogi Műhely, 2016)
The aim of the essay is to analyse a special moment, namely the moment of the end of a tyranny. An outstanding problem is how to judge the murder of a tyrant, and the occurrences that lead to that, because these acts actually make a chain of crimes, if they’re examined without the context. Breach of the peace, mayhem, mutiny, homicide, these are acts, that are against the moral code of humanity. They have been punished by criminal laws throughout history. Therefore it is crucial to examine the circumstances of this very act. These circumstances are actually the key factors to legitimise the aggression of a rebellion. Nevertheless the first thing that someone has to do during the analysis is to find a comprehensive definition that shows who is the person, who possesses the characteristic of an unjust despot.